2017
DOI: 10.1016/j.jcrc.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of veno-venous ECMO on the pharmacokinetics of Ritonavir, Darunavir, Tenofovir and Lamivudine

Abstract: To our knowledge, this is the first study reporting the PK profile of ART drugs during ECMO therapy. Based on our results, dose adjustment of ART drugs while on VV ECMO may be advisable. Further study of the PK profile of Lamivudine is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Based on the results from the study by Ghazi Suliman et al ( 23 ), the concentrations were observed in an expected range based on the model prediction while darunavir concentrations showed higher than the expected values for a typical individual with the regimen of 800 mg every 12 hours during the ECMO therapy. They suggested that the aggressive darunavir/ritonavir regimen of 800/100 mg every 12 hours as an antiretroviral therapy was appropriate in patients requiring the ECMO ( 23 ). We recommend not adjusting the darunavir/ritonavir dosing regimens as recommended for the COVID-19 but may increase the dose up to 800/100 mg every 12 hours as needed.…”
Section: Patients Receiving Ecmomentioning
confidence: 93%
See 1 more Smart Citation
“…Based on the results from the study by Ghazi Suliman et al ( 23 ), the concentrations were observed in an expected range based on the model prediction while darunavir concentrations showed higher than the expected values for a typical individual with the regimen of 800 mg every 12 hours during the ECMO therapy. They suggested that the aggressive darunavir/ritonavir regimen of 800/100 mg every 12 hours as an antiretroviral therapy was appropriate in patients requiring the ECMO ( 23 ). We recommend not adjusting the darunavir/ritonavir dosing regimens as recommended for the COVID-19 but may increase the dose up to 800/100 mg every 12 hours as needed.…”
Section: Patients Receiving Ecmomentioning
confidence: 93%
“…Darunavir (high logP, PB) has high possibility of drug lost in the circuit, whereas ritonavir has the moderate to high probability to be sequestrated due to the high PB and moderate logP. Based on the results from the study by Ghazi Suliman et al ( 23 ), the concentrations were observed in an expected range based on the model prediction while darunavir concentrations showed higher than the expected values for a typical individual with the regimen of 800 mg every 12 hours during the ECMO therapy. They suggested that the aggressive darunavir/ritonavir regimen of 800/100 mg every 12 hours as an antiretroviral therapy was appropriate in patients requiring the ECMO ( 23 ).…”
Section: Patients Receiving Ecmomentioning
confidence: 99%
“…A significant impact of hemodialysis on the pharmacokinetics of HCQ ( Tett et al, 1989 ) and LPV ( Gupta et al, 2008 ) is unlikely but requires confirmation since steady-state conditions are not achieved in COVID-19 patients. An impact of ECMO on chloroquine pharmacokinetics has been described ( Bagate et al, 2017 ) but no convincing data exist yet for LPV ( Ghazi Suliman et al, 2017 ). However, a significant impact of ECMO should be considered since several studies have shown altered PK profiles in this situation ( Ha and Sieg, 2017 ).…”
Section: Collection Of Covariates Affecting Dose-exposure Relationshimentioning
confidence: 99%
“…The result exhibited that the drug levels of ritonavir were lower than the expected concentrations for a typical individual in the population, suggesting that the PK of ritonavir changed during ECMO. 79 We suggest that COVID-19 patients with ECMO may need to increase the dose regimen of lopinavir/ritonavir and conduct therapeutic drug monitoring to achieve personalized treatment. Considering IFN-α is used as topical administration, we conferred that dosing adjustment is not required during ECMO.…”
Section: Antiviral Agents In Covid-19 Patients Receiving Ecmomentioning
confidence: 99%